Causes and Resolution of Buleleng Bali Customary Land Disputes - Sheila Ananda Siregar; Dilla Elfira Damanik; Albert Lodewyk Siahaan (Transpublika Publisher, 2025)
This study aims to examine the causal factors and mechanisms for resolving customary land disputes in Buleleng Regency, Bali. This research uses a qualitative method by collecting information from various sources such as legal regulations, previous research results, and literature studies. The novelty of this research lies in its focus on the role of Pakraman village as a customary institution in resolving disputes through mediation based on customary law (Awig-awig), as well as the collaborative approach between the community, customary institutions, and the government in handling land conflicts. The results show that customary land disputes in Buleleng are triggered by various factors including community ignorance of the legal status of customary land, unclear land boundaries, and increasing economic value of land. Conflict resolution is carried out through customary mediation with the stages of verification of reports, summoning parties and witnesses and custom-based decision-making. The conclusion of this research is that legal education, participatory mapping, land certification, and strengthening local regulations are very important to prevent conflicts and realise legal certainty for indigenous peoples in the management of customary land.